Analyzing the time-frequency impact of digital transformation on the improvement of service trade in Vietnam - Hung, Ngo Thai; Vinh, Dong Thanh; Dung, Vu Ngoc; San, Nguyen Trinh Linh (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
This study investigates the dynamic influence of digitalization (DG), gross domestic product (GDP), population (PO), and broad money supply (M2) on service trade (ST) in Vietnam from 1996 to 2022 using wavelet analysis and spectral Granger causality models. The results indicate that there is a positive nexus between variables during the sample period. While the relationship between broad money supply, population, and service trade is significant across different times and frequencies, the cases of ST-DG and ST-GDP are weak and insignificant at low frequencies. Moreover, Granger causality tests reveal that there exist bidirectional associations between the selected indicators. These findings suggest that Vietnam should focus on investment to enhance digitalization and expand the broad money supply, which would improve the service trade, attract foreign direct investment, and strengthen ties with other economies.